Latex composition and dip-molded article
By using a specific combination of conjugated diene-based polymers and polymer latex compositions, the problem of insufficient oil grip in the existing protective gloves under oil contact conditions is solved, and excellent oil grip performance is achieved.
Patent Information
- Application Number
- CN202180013682.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-18
- Filing Date
- 2021-02-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-02-15
AI Technical Summary
There is room for improvement in the grip performance (ie, oil grip) of existing protective gloves when they are wetted by oil, especially when used in contact with oil.
The latex composition including a latex of a conjugated diene polymer (A) having a glass transition temperature of 10°C or less and a latex of a polymer (B) having a glass transition temperature of more than 10°C is used to adjust the chemistry of both. The stability relationship and particle size form an excellent oil grip impregnated molded body.
The impregnated molded body with excellent oil grip under oil contact conditions is achieved, and the performance of protective gloves is improved.
Smart Images

Figure CN115103877B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a latex composition, and more particularly to a latex composition capable of forming a dip-molded body having excellent oil grip. Background Art
[0002] Conventionally, protective gloves made of fibers coated with rubber, resin, etc. to improve solvent resistance, grip, abrasion resistance, etc. have been used in various applications such as factory manufacturing, light work, engineering work, and agricultural work.
[0003] Since such protective gloves are usually used in contact with the human body, they are required to have excellent mechanical strength such as abrasion resistance and durability as well as excellent oil grip.
[0004] For example, Patent Document 1 discloses a method for producing a laminate, comprising a coagulant solution attaching step of attaching a coagulant solution to a fiber substrate and a coagulation step of coagulating a polymer by bringing a polymer latex into contact with the fiber substrate to which the coagulant solution is attached, thereby coagulating a polymer and forming a polymer layer on the fiber substrate, wherein the coagulant solution is formed by dissolving or dispersing 0.2 to 7.0 wt % of a metal salt as a coagulant and 0.1 to 7.0 wt % of an organic acid in a solvent.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: International Publication No. 2018 / 061868. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] According to the technology of Patent Document 1, a laminate having excellent softness and abrasion resistance and suitable for use in protective gloves can be obtained. However, there is room for improvement in the grip performance when wetted with oil (i.e., oil grip), and further improvement is required from the viewpoint of being applicable to applications where the laminate can be used even in a state of contact with oil.
[0010] The present invention has been made in view of such actual conditions, and an object of the present invention is to provide a latex composition capable of forming a dip-molded article having excellent oil gripping properties. Another object of the present invention is to provide a dip-molded article obtained by using such a latex composition.
[0011] Solutions for solving problems
[0012] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that in a latex composition comprising a latex of a conjugated diene polymer (A) having a glass transition temperature of less than 10°C and a latex of a polymer (B) having a glass transition temperature of more than 10°C, the above-mentioned problems can be solved by setting the chemical stability CS(A) of the latex of the conjugated diene polymer (A) and the chemical stability CS(B) of the latex of the polymer (B) with respect to CaCl2 to a specific relationship, thereby completing the present invention.
[0013] That is, according to the present invention, a latex composition can be provided, which comprises a latex of a conjugated diene polymer (A) having a glass transition temperature of less than 10°C and a latex of a polymer (B) having a glass transition temperature greater than 10°C, wherein, when the chemical stability relative to CaCl2 of the latex of the conjugated diene polymer (A) at a solid content concentration of 20% by weight is set to CS(A) (weight %), and the chemical stability relative to CaCl2 of the latex of the polymer (B) at a solid content concentration of 20% by weight is set to CS(B) (weight %), the value of (CS(B)-CS(A)) is greater than 0 weight %.
[0014] It is preferred that the volume average particle size of the polymer particles contained in the latex composition of the present invention is 250 nm or less.
[0015] The volume average particle size of the polymer particles contained in the latex composition of the present invention is preferably 200 nm or less.
[0016] In the latex composition of the present invention, the volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is preferably smaller than the volume average particle size of the particles of the conjugated diene polymer (A) contained in the latex of the conjugated diene polymer (A).
[0017] In the latex composition of the present invention, it is preferred that the volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is 200 nm or less.
[0018] In the latex composition of the present invention, it is preferred that the volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is 100 nm or less.
[0019] In the latex composition of the present invention, the solid content concentration is preferably 30% by weight or more.
[0020] In the latex composition of the present invention, the polymer (B) preferably has a sulfate group as a residue of a polymerization initiator at a polymer chain terminal.
[0021] In the latex composition of the present invention, the polymer (B) is preferably a polymer containing a styrene monomer unit or a (meth)acrylic acid ester monomer unit, and more preferably a polymer containing a (meth)acrylic acid ester monomer unit.
[0022] In the latex composition of the present invention, it is preferred that the conjugated diene polymer (A) comprises at least one selected from the group consisting of styrene-butadiene rubber, nitrile rubber and polyisoprene rubber.
[0023] In the latex composition of the present invention, the conjugated diene polymer (A) is preferably a carboxyl group-containing conjugated diene polymer.
[0024] In the latex composition of the present invention, the content ratio of the conjugated diene polymer (A) to the polymer (B) is preferably 1:9 to 9:1 in terms of the weight ratio of "conjugated diene polymer (A) : polymer (B)".
[0025] Furthermore, according to the present invention, there can be provided a dip-molded article produced using the latex composition.
[0026] The dip-molded article of the present invention is preferably a glove.
[0027] Effects of the Invention
[0028] According to the present invention, it is possible to provide a latex composition capable of forming a dip-molded article having excellent oil grip properties, and a dip-molded article obtained by using such a latex composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a diagram showing an example of a hydrochloric acid amount-electric conductivity curve obtained when the acid amount of a water-soluble polymer is measured. DETAILED DESCRIPTION
[0030] <Latex composition>
[0031] The latex composition of the present invention is a latex composition comprising a latex of a conjugated diene polymer (A) having a glass transition temperature of less than 10°C and a latex of a polymer (B) having a glass transition temperature greater than 10°C, wherein, when the chemical stability relative to CaCl2 of the latex of the conjugated diene polymer (A) at a solid content concentration of 20% by weight is set to CS(A) (weight %), and the chemical stability relative to CaCl2 of the latex of the polymer (B) at a solid content concentration of 20% by weight is set to CS(B) (weight %), the value of (CS(B)-CS(A)) is greater than 0 weight %.
[0032] The conjugated diene polymer (A) having a glass transition temperature of 10°C or less (hereinafter, appropriately referred to as "the latex of the conjugated diene polymer (A)") constituting the latex of the conjugated diene polymer (A) having a glass transition temperature of 10°C or less is not particularly limited as long as it is a polymer having a unit derived from a conjugated diene monomer, and examples thereof include nitrile rubber (NBR), natural rubber (NR), styrene-butadiene rubber (SBR), synthetic polyisoprene rubber (IR), polybutadiene rubber (BR), styrene-isoprene copolymer rubber, styrene-isoprene-styrene copolymer rubber, and the like. Among these, synthetic rubber is preferred, nitrile rubber (NBR), styrene-butadiene rubber (SBR), and synthetic polyisoprene rubber (IR) are more preferred, and conjugated diene polymers containing nitrile groups such as NBR (hereinafter, appropriately referred to as "nitrile group-containing conjugated diene polymers") are further preferred. Furthermore, these conjugated diene polymers may be conjugated diene polymers containing a carboxyl group (hereinafter referred to as "carboxyl group-containing conjugated diene polymer" as appropriate).
[0033] The nitrile group-containing conjugated diene polymer is not particularly limited, and for example, a nitrile group-containing conjugated diene polymer obtained by copolymerizing an α,β-ethylenically unsaturated nitrile monomer and a conjugated diene monomer and, if necessary, another copolymerizable ethylenically unsaturated acid monomer can be used.
[0034] The α,β-ethylenically unsaturated nitrile monomer is not particularly limited, and an ethylenically unsaturated compound having a nitrile group and preferably having 3 to 18 carbon atoms can be used. Examples of such α,β-ethylenically unsaturated nitrile monomers include acrylonitrile, methacrylonitrile, and halogenated acrylonitrile, and acrylonitrile is particularly preferred among these. In addition, these α,β-ethylenically unsaturated nitrile monomers may be used alone or in combination of two or more.
[0035] The content of the α,β-ethylenically unsaturated nitrile monomer units in the nitrile group-containing conjugated diene polymer is preferably 10 to 45% by weight, more preferably 20 to 40% by weight, and further preferably 25 to 40% by weight relative to all monomer units. By making the content of the α,β-ethylenically unsaturated nitrile monomer units within the above range, the obtained impregnated molded body can have excellent solvent resistance.
[0036] As the conjugated diene monomer, preferably, a conjugated diene monomer having 4 to 6 carbon atoms such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, chloroprene, etc., more preferably 1,3-butadiene and isoprene, and particularly preferably 1,3-butadiene. In addition, these conjugated diene monomers may be used alone or in combination of two or more.
[0037] The content of the conjugated diene monomer units in the nitrile group-containing conjugated diene polymer is preferably 40 to 80% by weight, more preferably 52 to 78% by weight, and further preferably 55 to 75% by weight relative to all monomer units. By making the content of the conjugated diene monomer units within the above range, the obtained impregnated molded body can have excellent flexibility.
[0038] Furthermore, the nitrile group-containing conjugated diene polymer may be a nitrile group-containing conjugated diene polymer obtained by copolymerizing a monomer forming an α,β-ethylenically unsaturated nitrile monomer unit, a monomer forming a conjugated diene monomer unit, and another copolymerizable ethylenically unsaturated acid monomer.
[0039] There are no particular limitations on such other copolymerizable ethylenically unsaturated acid monomers, and examples thereof include carboxyl group-containing ethylenically unsaturated monomers, monocarboxylic acid ester group-containing ethylenically unsaturated monomers, dicarboxylic acid diester group-containing ethylenically unsaturated monomers, sulfonic acid group-containing ethylenically unsaturated monomers, and phosphoric acid group-containing ethylenically unsaturated monomers. Among these, carboxyl group-containing ethylenically unsaturated monomers and dicarboxylic acid diester group-containing ethylenically unsaturated monomers are preferred from the viewpoint that the nitrile group-containing conjugated diene polymer can contain a carboxyl group, thereby resulting in the obtained impregnated molded body having better tensile strength and abrasion resistance.
[0040] The carboxyl group-containing ethylenically unsaturated monomer is not particularly limited, and examples thereof include: ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; ethylenically unsaturated polycarboxylic acids and anhydrides thereof such as fumaric acid, maleic acid, itaconic acid, maleic anhydride, and itaconic anhydride; and partial esters of ethylenically unsaturated polycarboxylic acids such as methyl maleate and methyl itaconate.
[0041] The monocarboxylate group-containing ethylenically unsaturated monomer is not particularly limited, and examples thereof include acrylic acid esters such as methyl acrylate; methacrylic acid esters such as methyl methacrylate; and crotonic acid esters such as methyl crotonate.
[0042] The dicarboxylic acid diester group-containing ethylenically unsaturated monomer is not particularly limited, and examples thereof include maleic acid diesters such as dimethyl maleate and itaconic acid diesters such as dimethyl itaconate and the like.
[0043] The sulfonic acid group-containing ethylenically unsaturated monomer is not particularly limited, and examples thereof include vinyl sulfonic acid, methyl vinyl sulfonic acid, styrene sulfonic acid, (meth)allyl sulfonic acid, 2-sulfonic ethyl (meth)acrylate, and 2-acrylamido-2-hydroxypropanesulfonic acid.
[0044] The phosphoric acid group-containing ethylenically unsaturated monomer is not particularly limited, and examples thereof include 3-chloro-2-phosphopropyl (meth)acrylate, 2-phosphoethyl (meth)acrylate, and 3-allyloxy-2-hydroxypropyl phosphate.
[0045] These other copolymerizable ethylenically unsaturated acid monomers can be used as alkali metal salts or ammonium salts, and can be used alone or in combination of two or more. Among the other copolymerizable ethylenically unsaturated acid monomers mentioned above, carboxyl-containing ethylenically unsaturated monomers are preferred, ethylenically unsaturated monocarboxylic acids are more preferred, acrylic acid and methacrylic acid are further preferred, and methacrylic acid is particularly preferred.
[0046] When the nitrile group-containing conjugated diene polymer contains units of other copolymerizable ethylenically unsaturated acid monomers, the content ratio of the units of other copolymerizable ethylenically unsaturated acid monomers relative to all monomer units is preferably 0.1 to 15% by weight, more preferably 1 to 10% by weight, and further preferably 2 to 8% by weight.
[0047] The latex of the nitrile group-containing conjugated diene polymer can be obtained, for example, by emulsion polymerization of a monomer mixture containing the above-mentioned monomers. In the emulsion polymerization, commonly used polymerization auxiliary materials such as emulsifiers, polymerization initiators, and molecular weight regulators can be used.
[0048] The emulsifier used in the emulsion polymerization is not particularly limited, and examples thereof include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants, and anionic surfactants are preferred. Specific examples of anionic surfactants include: fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, and sodium rosinate; alkylbenzene sulfonates such as sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, sodium decylbenzene sulfonate, potassium decylbenzene sulfonate, sodium hexadecylbenzene sulfonate, and potassium hexadecylbenzene sulfonate; alkyl sulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkyl sulfate ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate; sodium salt of β-naphthalenesulfonic acid formaldehyde condensate, and the like.
[0049] The amount of the emulsifier used in the emulsion polymerization is preferably 0.5 to 10 parts by weight, more preferably 1 to 8 parts by weight, based on 100 parts by weight of all the monomers used.
[0050] As a polymerization initiator, there is no particular limitation, and a free radical initiator is preferred. As a free radical initiator, there is no particular limitation, and examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as tert-butyl peroxide, cumene hydroperoxide, terpene hydroperoxide, di-tert-butyl peroxide, tert-butyl cumyl peroxide, acetyl peroxide, isobutyryl peroxide, octanoyl peroxide, dibenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, and tert-butyl peroxyisobutyrate; azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, azobiscyclohexanecarbonitrile, and methyl azobisisobutyrate, among which inorganic peroxides or organic peroxides are preferred, inorganic peroxides are more preferred, and persulfates are particularly preferred. These polymerization initiators can be used alone or in combination of two or more.
[0051] The amount of the polymerization initiator used is preferably 0.01 to 2 parts by weight, more preferably 0.05 to 1.5 parts by weight, based on 100 parts by weight of all the monomers used.
[0052] When a peroxide is used as a polymerization initiator, it can also be combined with a reducing agent to be used as a redox polymerization initiator. The reducing agent is not particularly limited, and examples thereof include: compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous cyclohexane; sulfonic acid compounds such as sodium methanesulfonate; amine compounds such as dimethylaniline; carboxylic acid compounds such as sodium ethylenediaminetetraacetate, etc. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight relative to 100 parts by weight of the peroxide.
[0053] The molecular weight modifier is not particularly limited, and examples thereof include: α-methylstyrene dimer; mercaptans such as tert-dodecyl mercaptan, n-dodecyl mercaptan, and octyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, dichloromethane, and dibromomethane; sulfur-containing compounds such as tetraethylthiuram disulfide, dipentamethylenethiuram disulfide, and diisopropylxanthate disulfide, etc. Among these, mercaptans are preferred, and tert-dodecyl mercaptan is more preferred. These molecular weight modifiers may be used alone or in combination of two or more.
[0054] The amount of the molecular weight modifier used varies depending on the type thereof, but is preferably 0.1 to 1.5 parts by weight, more preferably 0.2 to 1.0 parts by weight, based on 100 parts by weight of all monomers used.
[0055] Emulsion polymerization is usually carried out in water. The amount of water used is preferably 80 to 500 parts by weight, more preferably 100 to 200 parts by weight, based on 100 parts by weight of all monomers used.
[0056] In the emulsion polymerization, polymerization auxiliary materials other than the above-mentioned may be used as needed. Examples of polymerization auxiliary materials include chelating agents, dispersants, pH adjusters, deoxidizers, particle size adjusters, etc., and the types and amounts of these materials used are not particularly limited.
[0057] As a method for adding monomers, for example, there can be mentioned a method of adding the monomers to be used in a reaction container all at once; a method of adding them continuously or intermittently as the polymerization proceeds; a method of first adding a part of the monomers, reacting them to a specific conversion rate, and then adding the remaining monomers continuously or intermittently to polymerize, etc. Any method can be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be fixed or may be variable.
[0058] In addition, each monomer may be mixed in advance and then added to the reaction container, or may be added separately to the reaction container.
[0059] The polymerization temperature during emulsion polymerization is not particularly limited, but is usually 0 to 95° C., preferably 5 to 70° C. The polymerization time is not particularly limited, but is usually about 5 to 40 hours.
[0060] After the polymerization reaction is terminated, unreacted monomers may be removed and the solid content concentration and pH may be adjusted as desired.
[0061] The glass transition temperature of the conjugated diene polymer (A) constituting the conjugated diene polymer (A) latex is 10°C or less, preferably -45 to -10°C, more preferably -40 to -10°C, and particularly preferably -35 to -15°C. When the glass transition temperature of the conjugated diene polymer (A) is too high, the oil grip of the obtained impregnated molded body is poor. In addition, there is no particular limitation on the method for making the glass transition temperature of the conjugated diene polymer (A) within the above range, and examples thereof include a method for making the content ratio of each monomer unit constituting the conjugated diene polymer (A) within the above range.
[0062] As described later, based on the relationship between the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) with respect to CaCl2 and the chemical stability (CS(B)) of the latex of the polymer (B) with respect to CaCl2, the value of (CS(B)-CS(A)) only needs to be greater than 0% by weight. The chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) with respect to CaCl2 is preferably greater than 0% by weight and less than 0.5% by weight, more preferably 0.001 to 0.25% by weight, and even more preferably 0.005 to 0.1% by weight. By making the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) with respect to CaCl2 within the above range, the oil grip of the obtained impregnated molded body can be further improved.
[0063] In addition, as described below, in the present invention, the chemical stability (CS (A)) of the latex of the conjugated diene polymer (A) relative to CaCl2 can be measured as the chemical stability of the latex of the conjugated diene polymer (A) relative to CaCl2 when the solid content concentration is 20% by weight. First, the latex of the conjugated diene polymer (A) is diluted with distilled water, and a latex of the conjugated diene polymer (A) diluted to a solid content concentration of 20% by weight is prepared. In addition, 5 to 10 kinds of CaCl2 aqueous solutions of different concentrations (weight %) between 0.01 and 5% by weight are prepared. Here, the change in chemical stability when the CaCl2 concentration is changed has a tendency to be greater when the CaCl2 concentration is lower and smaller when the CaCl2 concentration is higher. That is, there is a tendency that at a relatively low concentration of less than 0.3 wt%, a concentration change of about 0.1 wt% will cause a change in chemical stability, while at a relatively high concentration of more than 0.3 wt%, the concentration can be varied at intervals of 0.2 to 0.25 wt%, and the change in chemical stability can be fully confirmed. This point should be kept in mind when preparing a CaCl2 aqueous solution. The lower the CaCl2 concentration, the smaller the interval of the CaCl2 concentration, and the higher the CaCl2 concentration, the larger the interval of the CaCl2 concentration. Prepare about 5 to 10 kinds of CaCl2 aqueous solutions. Next, weigh 6 to 7 g of the prepared CaCl2 aqueous solutions of different concentrations in a dish, and add 0.03 to 0.04 g of the diluted latex of the conjugated diene polymer (A) thereto. After the addition, let it stand for 1 minute, and then gently shake the dish to mix. After mixing, confirm the formation of agglomerates by visual inspection. Then, among the CaCl2 aqueous solutions to which no coagulation occurs even when a diluted latex of a conjugated diene polymer (A) is added dropwise, the CaCl2 concentration of the CaCl2 aqueous solution having the maximum CaCl2 concentration is taken as the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A).
[0064] In addition, the volume average particle size of the particles of the conjugated diene polymer (A) constituting the latex of the conjugated diene polymer (A) is preferably 30 to 1000 nm, more preferably 50 to 500 nm, further preferably 70 to 200 nm, and particularly preferably 90 to 150 nm. By making the volume average particle size of the particles of the conjugated diene polymer (A) within the above range, in the obtained impregnated molded body, the polymer (B) having a glass transition temperature greater than 10°C can be better microdispersed in the conjugated diene polymer (A), thereby improving the wear resistance. In addition, the volume average particle size of the particles of the conjugated diene polymer (A) constituting the latex of the conjugated diene polymer (A) can be measured using, for example, a light scattering diffraction particle measuring device.
[0065] The percentage of the tetrahydrofuran insoluble content of the polymer (A) is not particularly limited, but is preferably 20 to 80% by weight, more preferably 30 to 70% by weight, and further preferably 40 to 60% by weight. The percentage of the tetrahydrofuran insoluble content of the polymer (A) is an indicator of the amount of gel content of the polymer (A).
[0066] As a method for measuring the percentage of tetrahydrofuran-insoluble components of polymer (A), the following method can be cited. That is, first, a latex of polymer (A) is applied to a substrate by a casting method or the like, and dried to obtain a dry film, and the weight of the dry film is measured. Next, the obtained dry film is immersed in tetrahydrofuran at 25° C. for 24 hours. Next, the immersed film is dried at 105° C. for 3 hours to remove tetrahydrofuran, and the weight of the film after the removal of tetrahydrofuran is measured. From these weight measurement results, the percentage of tetrahydrofuran-insoluble components can be calculated.
[0067] In addition, the polymer (B) having a glass transition temperature greater than 10°C (hereinafter, appropriately referred to as "polymer (B)") constituting the latex of the polymer (B) having a glass transition temperature greater than 10°C (hereinafter, appropriately referred to as "latex of polymer (B)") is not particularly limited, as long as the glass transition temperature is greater than 10°C and the chemical stability with respect to CaCl2 when prepared as a latex is higher than that of the latex of the conjugated diene polymer (A). That is, when the glass transition temperature is greater than 10°C and the chemical stability with respect to CaCl2 of the latex of the polymer (B) at a solid content concentration of 20% by weight is CS(B) (wt%), the value of (CS(B)-CS(A)) may be greater than 0% by weight in relation to the chemical stability with respect to CaCl2 of the latex of the conjugated diene polymer (A) described above.
[0068] In addition, the chemical stability CS(B) (weight %) of the latex of the polymer (B) relative to CaCl2 when the solid content concentration is 20 weight % can be measured in the same way as the method for measuring the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) relative to CaCl2.
[0069] Such polymer (B) is not particularly limited, and examples thereof include acrylic resin, PTFE resin, acrylonitrile-styrene (AS) resin, polyurethane, etc., wherein acrylic resin is preferred from the viewpoint of high improvement effect of oil grip. In addition, one of these polymers can be used alone, or two or more can be used in combination. In addition, as polymer (B), when two or more polymers are used in combination, the chemical stability (CS (B)) of the latex containing the two or more polymers used in combination relative to CaCl2 is calculated based on the relationship with the chemical stability (CS (A)) of the latex of the conjugated diene polymer (A) relative to CaCl2, as long as (CS (B) - CS (A)) is greater than 0 weight %. As an example, when the first polymer and the second polymer are combined to form the polymer (B), even if the latex containing the first polymer alone satisfies (CS(B)-CS(A)) greater than 0 wt%, and the latex containing the second polymer alone has (CS(B)-CS(A)) of 0 wt% or less, the latex containing both the first polymer and the second polymer only needs to satisfy (CS(B)-CS(A)) greater than 0 wt%. For example, when the polymer (B) is a combination of an acrylic resin and a polymer other than the acrylic resin, examples of the polymer used in combination with the acrylic resin include polystyrene resin, PTFE resin, acrylonitrile-styrene (AS) resin, polyurethane, and the like. At this time, the content ratio of the acrylic resin to the polymer other than the acrylic resin is preferably 1:9 to 9:1, and more preferably 3:7 to 7:3, in terms of the weight ratio of "acrylic resin: polymer other than the acrylic resin".
[0070] Examples of acrylic resins include homopolymers of acrylate, methacrylate, acrylic acid or methacrylic acid; copolymers of acrylate and acrylic acid; copolymers of acrylate and methacrylic acid; copolymers of methacrylate and acrylic acid; copolymers of methacrylate and methacrylic acid; copolymers of acrylate, methacrylate and acrylic acid; copolymers of acrylate, methacrylate and methacrylic acid; and copolymers of acrylate, methacrylate, acrylic acid and methacrylic acid. Among these, homopolymers of acrylate, methacrylate, acrylic acid or methacrylic acid are preferably used, and homopolymers of methacrylate are preferably used.
[0071] Examples of the acrylic ester used to form the acrylic resin include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, sec-pentyl acrylate, isopentyl acrylate, neopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, neohexyl acrylate, sec-hexyl acrylate, and tert-hexyl acrylate. Among them, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, and n-butyl acrylate are preferred, and methyl acrylate is more preferred.
[0072] Examples of the methacrylate used to form the acrylic resin include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, sec-pentyl methacrylate, isopentyl methacrylate, neopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, neohexyl methacrylate, sec-hexyl methacrylate, and tert-hexyl methacrylate. Among them, methyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, and n-butyl methacrylate are preferred, methyl methacrylate is more preferred, and a homopolymer of methyl methacrylate (polymethyl methacrylate) is particularly preferred.
[0073] The acrylic resin used as the polymer (B) may be an acrylic resin obtained by copolymerizing other monomers copolymerizable with an acrylic acid ester monomer, a methacrylic acid ester monomer, an acrylic acid monomer, or a methacrylic acid monomer.
[0074] As other monomers that can be copolymerized, there can be mentioned α-olefin monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene; aromatic monomers such as styrene, α-methylstyrene, and vinylpyridine; α,β-ethylenically unsaturated polycarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; α,β-ethylenically unsaturated polycarboxylic acid monoesters such as monomethyl maleate, monoethyl maleate, and monoethyl itaconate; α,β-ethylenically unsaturated polycarboxylic acid polyesters such as dimethyl maleate, di-n-butyl fumarate, dimethyl itaconate, and di-2-ethylhexyl itaconate; vinyl ester monomers such as vinyl acetate and vinyl propionate; α,β-ethylenically unsaturated monocarboxylic acid amides such as acrylamide and methacrylamide; N-substituted maleimides; vinyl ether monomers such as vinyl methyl ether, vinyl ethyl ether, and vinyl hexadecyl ether; vinylidene compounds such as vinylidene chloride, etc. Among these, aromatic monomers are preferred, and styrene is more preferred. The content ratio of other copolymerizable monomer units is preferably 1 to 99% by weight, more preferably 5 to 95% by weight.
[0075] The method for producing the latex of the acrylic resin used as the polymer (B) is not particularly limited as long as it is a method capable of polymerizing the above-mentioned monomers, and examples thereof include known emulsion polymerization, seed emulsion polymerization, and microsuspension polymerization methods utilizing radical polymerization.
[0076] In addition, polymer (B) preferably uses persulfate such as sodium persulfate, potassium persulfate, ammonium persulfate as a polymerization initiator. By using persulfate as a polymerization initiator, polymer (B) can have a sulfate group at the end of the polymer chain as a residue of the polymerization initiator, thereby making the chemical stability of the latex of polymer (B) more excellent.
[0077] The weight average molecular weight (Mw) of the acrylic resin as the polymer (B) is not particularly limited, but is preferably 10,000 to 10,000,000, and more preferably 10,000 to 5,000,000.
[0078] The glass transition temperature of the polymer (B) constituting the latex of the polymer (B) is higher than 10°C, preferably higher than 30°C, more preferably higher than 70°C, further preferably higher than 95°C, and particularly preferably higher than 105°C. The upper limit of the glass transition temperature of the polymer (B) is not particularly limited, but is preferably lower than 200°C, more preferably lower than 150°C.
[0079] Furthermore, in the latex composition of the present invention, the difference (CS(B)-CS(A)) between the chemical stability (CS(B)) of the latex of the polymer (B) with respect to CaCl2 and the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) with respect to CaCl2 is greater than 0% by weight, preferably 0.1 to 40.0% by weight, more preferably 0.3 to 40.0% by weight, further preferably 0.5 to 5% by weight, and particularly preferably 0.7 to 2% by weight. When the difference in chemical stability (CS(B)-CS(A)) is too low, the oil grip of the obtained impregnated molded body is poor.
[0080] The chemical stability (CS(B)) of the latex of the polymer (B) with respect to CaCl2 is calculated in relation to the chemical stability (CS(A)) of the latex of the conjugated diene polymer (A) with respect to CaCl2. As long as (CS(B)-CS(A)) is within the above range, the chemical stability (CS(B)) of the latex of the polymer (B) with respect to CaCl2 is not particularly limited, but is preferably 0.1 to 40.0% by weight, more preferably 0.2 to 40.0% by weight, further preferably 0.3 to 40.0% by weight, further preferably 0.5 to 5% by weight, and particularly preferably 0.7 to 2% by weight. By setting the chemical stability (CS(B)) of the latex of the polymer (B) with respect to CaCl2 within the above range, the oil grip of the obtained dip molded body can be further improved.
[0081] Among the latex compositions of the present invention, a latex composition obtained by mixing a latex of a conjugated diene polymer (A) having a glass transition temperature of 10° C. or less and a latex of a polymer (B) having a glass transition temperature of more than 10° C. in a latex state is preferred. When a dip molded article is obtained using such a latex composition by mixing the latex of the conjugated diene polymer (A) and the latex of the polymer (B) in a latex state, liquid dripping during molding can be further suppressed, and the oil gripping property of the obtained dip molded article can be made further excellent.
[0082] In particular, by mixing the latex of the conjugated diene polymer (A) with the latex of the polymer (B) in a latex state, the particles of the conjugated diene polymer (A) and the particles of the polymer (B) can be uniformly microdispersed in the latex composition. Then, when the impregnation molded body is made by impregnation molding, in the obtained impregnation molded body, the polymer (B) can be microdispersed in the matrix of the conjugated diene polymer (A) so that they can be coprecipitated. Therefore, by the effect of the microdispersed polymer (B), the oil grip of the obtained impregnation molded body can be further improved. In addition, in the present invention, it is preferred to mix the latex of the conjugated diene polymer (A) and the latex of the polymer (B) in a latex state to form a latex composition, but the latex composition of the present invention can be a latex composition in which the particles of the conjugated diene polymer (A) and the particles of the polymer (B) are dispersed in an aqueous medium, and the latex composition obtained by mixing these latexes is not particularly limited.
[0083] When the glass transition temperature of the polymer (B) constituting the latex of the polymer (B) is too low, the oil grip of the obtained dip molded article is poor. In addition, the method for making the glass transition temperature of the polymer (B) within the above range is not particularly limited, and for example, when a latex of a vinyl chloride resin is used as the latex of the polymer (B), the content of the vinyl chloride monomer unit in the vinyl chloride resin is preferably 50% by weight or more, more preferably 75% by weight or more.
[0084] From the viewpoint of further improving the oil grip of the obtained impregnated molded body, the volume average particle size of the particles of the polymer (B) constituting the latex of the polymer (B) is preferably smaller than the volume average particle size of the particles of the conjugated diene polymer (A) constituting the latex of the conjugated diene polymer (A).
[0085] The volume average particle size of the particles of the polymer (B) constituting the latex of the polymer (B) is preferably 1 to 200 nm, more preferably 5 to 160 nm, further preferably 5 to 120 nm, further preferably 10 to 100 nm, and particularly preferably 20 to 80 nm. By making the volume average particle size of the particles of the polymer (B) within the above range, in the obtained impregnated molded body, the polymer (B) can be better microdispersed in the conjugated diene polymer (A), thereby improving the wear resistance. In addition, the volume average particle size of the particles of the polymer (B) constituting the latex of the polymer (B) can be measured using, for example, a light scattering diffraction particle measuring device (manufactured by Beckman Coulter, trade name "LS-230").
[0086] The percentage of tetrahydrofuran-insoluble components of polymer (B) is not particularly limited, and is preferably 5 to 60% by weight, more preferably 10 to 50% by weight, and further preferably 20 to 40% by weight. The percentage of tetrahydrofuran-insoluble components of polymer (B) is an indicator of the amount of gel component of polymer (B). By making the percentage of tetrahydrofuran-insoluble components of polymer (B) within the above range, the chemical stability of the obtained latex composition can be further improved, and further, the oil grip of the obtained dip molded body can be further improved. In addition, the percentage of tetrahydrofuran-insoluble components of polymer (B) can be measured by the same method as the percentage of tetrahydrofuran-insoluble components of polymer (A).
[0087] The content of the conjugated diene polymer (A) and the content of the polymer (B) in the latex composition of the present invention are not particularly limited. The content of the conjugated diene polymer (A) in 100 parts by weight of the polymer component contained in the latex composition (when only the conjugated diene polymer (A) and the polymer (B) are contained as polymer components, the content of the conjugated diene polymer (A) and the polymer (B) is 100 parts by weight in total). The content of the conjugated diene polymer (A) is preferably 40 parts by weight or more, more preferably 40 to 95 parts by weight, and even more preferably 40 to 80 parts by weight. In addition, the content of the polymer (B) is preferably 5 to 80 parts by weight, more preferably 10 to 70 parts by weight, and even more preferably 20 to 60 parts by weight relative to 100 parts by weight of the polymer component contained in the latex composition. Furthermore, the content ratio of the conjugated diene polymer (A) to the polymer (B) in the latex composition of the present invention is preferably 99:1 to 1:99, more preferably 90:10 to 10:90, further preferably 80:20 to 20:80, and particularly preferably 75:25 to 25:75, in terms of the weight ratio of "conjugated diene polymer (A): polymer (B)". By setting the contents of the conjugated diene polymer (A) and the polymer (B) to the above ranges, the oil grip of the obtained dip molded article can be further improved.
[0088] Furthermore, the latex composition of the present invention may further contain a water-soluble polymer.
[0089] Examples of the water-soluble polymer include vinyl compounds such as polyvinyl alcohol and polyvinyl pyrrolidone; cellulose derivatives such as hydroxyethyl cellulose, hydroxypropyl cellulose, and carboxymethyl cellulose and their salts; polycarboxylic acid compounds such as polyacrylic acid and their sodium salts; polyoxyethylene derivatives such as polyethylene glycol ether, etc. As the water-soluble polymer, cellulose derivatives and their salts are preferred, and carboxymethyl cellulose and its sodium salt are more preferred. The content of the water-soluble polymer is preferably 0.01 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, relative to 100 parts by weight of the polymer component contained in the first latex composition.
[0090] The acid amount of the water-soluble polymer is not particularly limited, but is preferably 10 mmol / g or less. That is, the first latex composition used in the present invention preferably contains a water-soluble polymer having an acid amount of 10 mmol / g or less.
[0091] When the latex composition of the present invention contains a water-soluble polymer having an acid content of 10 mmol / g or less in addition to the latex of the conjugated diene polymer (A) and the latex of the polymer (B), the oil gripping property of the obtained dip molded article can be further improved.
[0092] The acid amount of the water-soluble polymer is preferably 10 mmol / g or less, more preferably 5 mmol / g or less, and further preferably 2.5 mmol / g or less. The lower limit of the acid amount of the water-soluble polymer is not particularly limited, but is usually 0.001 mmol / g or more. By making the acid amount of the water-soluble polymer within the above range, the oil grip of the obtained dip molded body is more excellent.
[0093] The water-soluble polymer having an acid content of 10 mmol / g or less is not particularly limited, and examples thereof include vinyl compounds such as polyvinyl alcohol and polyvinyl pyrrolidone; carboxylic acid-modified vinyl compounds such as carboxylic acid-modified polyvinyl alcohol and carboxylic acid-modified polyvinyl pyrrolidone; cellulose derivatives such as hydroxyethyl cellulose, hydroxypropyl cellulose, and carboxymethyl cellulose, and salts thereof; polyoxyethylene derivatives such as polyethylene glycol ether, etc. These water-soluble polymers may be used alone or in combination of two or more.
[0094] The acid amount of the water-soluble polymer can be measured by, for example, the following method.
[0095] First, in a 200 ml glass container washed with distilled water, 50 g of an aqueous solution of a water-soluble polymer to which distilled water was added so as to adjust the solid content concentration to 0.2 to 1% (the solid content of the water-soluble polymer in 50 g of the aqueous solution of the water-soluble polymer is W (g)) was added, and a solution conductivity meter (CM-117 manufactured by Kyoto Electronics Co., Ltd., probe type used: K-121) was set, and stirring was started. Then, while stirring was continued, 0.1 normal sodium hydroxide was added so that the pH of the aqueous solution was 12 or more, and the conductivity was measured after 6 minutes, and the obtained measured value was taken as the conductivity at the start of the measurement. Next, 0.5 ml of 0.1 normal hydrochloric acid was added to the water-soluble polymer aqueous solution, and the conductivity was measured after 30 seconds, and 0.5 ml of 0.1 normal hydrochloric acid was added again, and the conductivity was measured after 30 seconds, and this operation was repeated at intervals of 30 seconds until the conductivity reached more than twice the conductivity at the start of the measurement. Then, the obtained conductivity data was plotted on a graph with the vertical axis: conductivity (mS) and the horizontal axis: the cumulative amount of hydrochloric acid added (mmol), and the following was obtained: Figure 1 The hydrochloric acid amount-conductivity curve having two inflection points shown in FIG. 1 is used. The X coordinates of the obtained two inflection points and the X coordinates at the end of the addition of hydrochloric acid are set as P1, P2 and P3 in order from the smallest value. The data in the three intervals of the X coordinate from zero to P1, from P1 to P2, and from P2 to P3 are respectively obtained by the least square method to obtain approximate straight lines L1, L2 and L3. In addition, the X coordinate of the intersection of L1 and L2 is set as A1 (mmol), and the X coordinate of the intersection of L2 and L3 is set as A2 (mmol). Then, the acid amount per 1g of the water-soluble polymer is obtained by the following formula.
[0096] Acid amount per 1g of water-soluble polymer = (A2-A1) / W (mmol / g)
[0097] In addition, when two or more water-soluble polymers are used in combination, the acid amount of the water-soluble polymer mixture obtained by mixing the respective water-soluble polymers in the same ratio as the presence ratio of the respective water-soluble polymers in the latex composition of the present invention can be measured in the same manner as described above, and the acid amount of the water-soluble polymer mixture obtained can be taken as the acid amount of the water-soluble polymer.
[0098] The viscosity of a 4 wt % aqueous solution of a water-soluble polymer is not particularly limited, but is preferably 1 mPa·s or more, more preferably 10 mPa·s or more, preferably 20000 mPa·s or less, and more preferably 10000 mPa·s or less. The viscosity of a 1 wt % aqueous solution of a water-soluble polymer is not particularly limited, but is preferably 1 mPa·s or more, more preferably 10 mPa·s or more, preferably 20000 mPa·s or less, and more preferably 10000 mPa·s or less. The viscosity of an aqueous solution of a water-soluble polymer can be measured, for example, using a B-type viscometer at 25° C. and a rotation speed of 6 rpm.
[0099] The water-soluble polymer may be any polymer that is soluble in water. The solubility of the water-soluble polymer in water is not particularly limited, but is preferably 1 g or more, more preferably 7 g or more, and particularly preferably 10 g or more in 100 g of water at 25° C. The upper limit of the solubility of the water-soluble polymer in water is not particularly limited, but is usually 1,000,000 g or less.
[0100] The weight average molecular weight (Mw) of the water-soluble polymer is not particularly limited, but is preferably 100 or more, more preferably 1,000 or more, and is preferably 5,000,000 or less, more preferably 3,000,000 or less.
[0101] The amount of the water-soluble polymer is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 0.15 to 4.5 parts by weight relative to 100 parts by weight of the polymer component contained in the latex composition of the present invention. When the amount of the water-soluble polymer is within the above range, the obtained dip molded article has better oil grip.
[0102] The volume average particle size of the polymer particles in the latex composition of the present invention is preferably 30 to 250 nm, more preferably 30 to 200 nm, further preferably 50 to 180 nm, and particularly preferably 80 to 150 nm. By setting the volume average particle size of the polymer particles in the latex composition to the above range, the storage stability of the latex composition can be improved, and the oil grip of the obtained dip molded product can be improved. In addition, the volume average particle size of the polymer particles in the latex composition of the present invention can be measured using, for example, a light scattering diffraction particle measuring device.
[0103] The solid content concentration of the latex composition of the present invention is preferably 20 to 65% by weight, more preferably 30 to 60% by weight, and further preferably 35 to 55% by weight. By setting the solid content concentration of the latex composition to the above range, the conveying efficiency of the latex composition can be improved, and the viscosity of the polymer latex can be made appropriate, thereby improving the handling properties of the latex composition.
[0104] As a method for adjusting the solid content concentration of the latex composition of the present invention to the above range, for example, there can be mentioned a method of adjusting the solid content concentration of each component such as the latex of the conjugated diene polymer (A), and a method of adjusting by a concentration treatment or a dilution treatment described later. Among these, the method of adjusting by a concentration treatment is preferred from the viewpoint of productivity.
[0105] The pH of the latex composition of the present invention is preferably 5 to 13, more preferably 7 to 10, and even more preferably 7.5 to 9. By setting the pH of the latex composition to the above range, mechanical stability can be improved, the generation of coarse aggregates during the transportation of the latex composition can be suppressed, and the viscosity of the polymer latex can be made appropriate, thereby improving the handling properties of the latex composition.
[0106] In addition, fillers such as carbon black, silica, calcium carbonate, aluminum silicate, magnesium silicate, calcium silicate, magnesium oxide, zinc (meth)acrylate, magnesium (meth)acrylate, and titanium oxide may be added to the latex composition of the present invention. In addition, various additives such as antioxidants, antioxidants, preservatives, antibacterial agents, wetting agents, dispersants, pigments, dyes, reinforcing agents, and pH adjusters may be added to the first latex composition used in the present invention in a predetermined amount in addition to the above-mentioned water-soluble salts and fillers as needed.
[0107] The latex composition of the present invention can be prepared, for example, by mixing the above-mentioned components and then, as needed, performing a concentration treatment or a dilution treatment. The order of mixing the components is not particularly limited. From the viewpoint of further improving the dispersibility of the components, it is preferred to pre-mix the latex of the conjugated diene polymer (A) and the latex of the polymer (B), and then add a thickener and the components formulated as needed and mix them. There is no particular limitation on the method of mixing the latex of the conjugated diene polymer (A) and the latex of the polymer (B). From the viewpoint of further improving the dispersibility, it is preferred to mix the latex of the conjugated diene polymer (A) and the latex of the polymer (B) in a latex state (latex mixture).
[0108] The latex composition of the present invention is preferably a latex composition obtained by a concentration treatment. The concentration treatment method is not particularly limited, and examples thereof include reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, and the like. Among these, a concentration method accompanied by heating is preferred, and reduced pressure distillation accompanied by heating is more preferred. By adopting a concentration method accompanied by heating, it is possible to reduce odor-causing bacteria or inhibit the proliferation of odor-causing bacteria, and the low odor property of the latex composition can be made excellent.
[0109] In the concentration method with heating, the heating temperature is preferably 50° C. to 100° C. Furthermore, in the reduced pressure distillation, the pressure is preferably 20 kPa to 90 kPa.
[0110] The concentration treatment may be carried out on a mixture containing a part of the components formulated in the latex composition, or on a mixture containing all the components formulated in the latex composition. From the viewpoint of the dispersibility of the latex composition and production efficiency, it is preferred to carry out the concentration treatment on a mixture of the latex of the conjugated diene polymer (A) and the latex of the polymer (B).
[0111] That is, as a method for producing the latex composition of the present invention, the following method is preferred: a latex of a conjugated diene polymer (A) and a latex of a polymer (B) are pre-mixed, and then the obtained mixture is concentrated to increase the solid content concentration, and then the components formulated as required are added and mixed to thereby adjust the solid content concentration to the above-mentioned range.
[0112] <Impregnation Molding Body>
[0113] The dip-molded article of the present invention is a molded article obtained using the latex composition of the present invention, and is usually obtained by dip molding using the latex composition of the present invention.
[0114] Since the dip molded article of the present invention is a molded article obtained using the latex composition of the present invention, it has at least a polymer layer containing the conjugated diene polymer (A) having a glass transition temperature of 10° C. or less and the polymer (B) having a glass transition temperature of more than 10° C. The preferred range of the content ratio of the conjugated diene polymer (A) and the polymer (B) in the dip molded article of the present invention is the same as the range described as the preferred range of the content ratio of the conjugated diene polymer (A) and the polymer (B) in the latex composition of the present invention.
[0115] The dip-molded article of the present invention may be a film-molded article formed of a dip-molded latex composition obtained by dipping a dip-molded mold into a dip-molded latex composition such as the latex composition of the present invention, or may be a laminate of a substrate and a polymer layer formed of a dip-molded latex composition obtained by dipping a substrate into a dip-molded latex composition. Hereinafter, the dip-molded article of the present invention is described as an example of a laminate of a substrate and a polymer layer formed of a dip-molded latex composition, but the present invention is not limited to such a mode.
[0116] The base material is not particularly limited, but when the dip-molded article of the present invention is used as a protective glove, a fiber base material can be preferably used. The fiber base material is not particularly limited, and for example, a twisted yarn of a single fiber can be used and the twisted yarn can be knitted into a glove shape. The average thickness of the fiber base material is preferably 50 to 3000 μm, more preferably 100 to 2000 μm.
[0117] The dip-molded article of the present invention can be produced, for example, by immersing a substrate in a latex composition for dip molding to form a polymer layer formed of the latex composition for dip molding on the substrate. In this case, it is preferred that the substrate be immersed in the latex composition for dip molding in a state where the substrate is previously covered with a molding mold of a desired shape.
[0118] The molding die for substrate coating is not particularly limited, and various molds made of porcelain, glass, metal, plastic, etc. can be used. The shape of the molding die may be set to a desired shape according to the shape of the final product. For example, when the dip-molded body of the present invention is used as a protective glove, it is preferable to use a molding die for various gloves such as a molding die having a shape from the wrist to the fingertips as the molding die for substrate coating.
[0119] In addition, before immersing the substrate in the latex composition for dip molding, it is preferred to immerse the substrate in a coagulant solution in advance so that the coagulant solution adheres to the substrate. At this time, it is preferred to immerse the substrate in the coagulant solution in a state where the substrate is pre-covered with a molding mold of the desired shape. As the molding mold of the desired shape, the above-mentioned molding mold can be cited. In addition, the coagulant solution is adhered to the substrate, and after the coagulant solution is adhered to the substrate, it is preferred to remove the solvent contained in the coagulant solution by drying. The drying temperature at this time is not particularly limited and can be selected according to the solvent used. It is preferably 10 to 80°C, and more preferably 15 to 70°C. In addition, the drying time is not particularly limited, and is preferably 600 to 1 second, and more preferably 300 to 5 seconds.
[0120] Next, the substrate to which the coagulant solution is attached is immersed in the dip molding latex composition while covering a molding die of a desired shape, thereby coagulating the dip molding latex composition and attaching a polymer layer formed of the dip molding latex composition to the substrate.
[0121] Then, it is preferred that the substrate is immersed in the latex composition for dip molding and then dried. The drying temperature at this time is not particularly limited, but is preferably 10 to 80° C., more preferably 15 to 80° C. In addition, the drying time is not particularly limited, but is preferably 120 minutes to 5 seconds, more preferably 60 minutes to 10 seconds.
[0122] When a latex composition containing a sulfur-based crosslinking agent is used as the latex composition for dip molding, a pre-ripened (also referred to as pre-vulcanized) latex composition may be used as the latex composition for dip molding.
[0123] The temperature conditions during aging are not particularly limited, but are preferably 20 to 50° C. In addition, from the viewpoint of preventing the substrate from peeling off from the polymer layer formed from the latex composition for dip molding and improving the abrasion resistance when the obtained dip-molded body is used as a protective glove, the aging time is preferably 4 hours to 120 hours, and more preferably 24 hours to 72 hours.
[0124] Next, the latex composition for dip molding adhered to the substrate is preferably heated to crosslink the polymer component contained in the latex composition for dip molding.
[0125] The heating temperature for crosslinking is preferably 60 to 160° C., more preferably 80 to 150° C. By setting the heating temperature to the above range, the time required for the crosslinking reaction can be shortened, the productivity of the impregnated molded body can be improved, and the oxidative degradation of the polymer component caused by excessive heating can be suppressed, thereby improving the physical properties of the obtained impregnated molded body. The heating time for crosslinking can be appropriately selected according to the heating temperature, and is usually 5 to 120 minutes.
[0126] In addition, for the dip-molded body obtained in this way, it is preferred to remove water-soluble impurities (emulsifier, water-soluble polymer, coagulant, etc.) from the polymer layer by immersing the polymer layer formed on the substrate in warm water at 20 to 80° C. for about 0.5 to 60 minutes as needed. Such a treatment of immersing the polymer layer in warm water can be performed after cross-linking the polymer components in the polymer layer, but is preferably performed before cross-linking the polymer components in the polymer layer from the viewpoint of being able to more efficiently remove water-soluble impurities.
[0127] After immersion in warm water, drying may be further performed. The drying temperature and drying time at this time are not particularly limited and may be the same as the drying temperature and drying time in the drying step after immersion in the latex composition for dip molding described above.
[0128] Furthermore, as described above, the polymer layer can be formed on the substrate in a state where the substrate is coated on the molding die, and then the substrate is separated from the molding die (or demoulded) to obtain an impregnated molded body. As a method of separation, it is possible to adopt a method of peeling off from the molding die by hand, or by water pressure or compressed air pressure.
[0129] Before or after the dip-molded body is separated from the molding die, it may be further subjected to a heat treatment (post-crosslinking step) at a temperature of 60 to 130° C. for 10 to 120 minutes. In addition, after the dip-molded body is separated from the molding die, a surface treatment layer may be formed on the inner and / or outer surfaces of the dip-molded product by chlorination treatment, coating treatment, etc.
[0130] Since the dip molded article of the present invention obtained in this way is a dip molded article in which a polymer layer formed from the latex composition of the present invention is formed on a substrate by coagulation using a coagulant, the film thickness is preferably 0.05 to 1.0 mm, more preferably 0.06 to 0.8 mm, and further preferably 0.07 to 0.7 mm, thereby improving the wear resistance of the obtained dip molded article. In addition, in general, when a dip molded article is made into a thicker film, there is a tendency that the oil gripping property tends to decrease, but the dip molded article according to the present invention can achieve excellent oil gripping property even when it is made into a thicker film.
[0131] In addition, as the dip molded body of the present invention, in addition to the above-mentioned substrate and the polymer layer formed by the latex composition of the present invention, it can also further have other polymer layers. That is, it can also be a dip molded body having two or more polymer layers on the substrate. As such other polymer layers, there is no particular limitation, and it is preferred to use a polymer layer formed by a latex composition other than the latex composition of the present invention. As such a latex composition, for example: a latex composition containing a nitrile-containing conjugated diene polymer, a latex of styrene-butadiene rubber (SBR), a latex of a synthetic polyisoprene rubber (IR), etc. can be cited. Among these, from the viewpoint of being able to make the obtained dip molded body excellent in oil permeability, it is preferred to use a latex composition containing a latex of a nitrile-containing conjugated diene polymer. In addition, as the latex of the nitrile-containing conjugated diene polymer, for example, a latex of a nitrile-containing conjugated diene polymer as an example of the latex of the above-mentioned conjugated diene polymer (A) can be preferably used. Furthermore, from the viewpoint of being able to further improve the oil gripping property of the obtained dip-molded article, the polymer layer formed from the latex composition of the present invention is preferably the outermost layer.
[0132] When two or more polymer layers are provided, the thickness of each polymer layer is not particularly limited, but for example, the total thickness of all polymer layers is preferably within the range of the preferred thickness of the polymer layer formed from the latex composition of the present invention.
[0133] In addition, the manufacturing method in the case of forming a method having two or more polymer layers is not particularly limited, and the following method can be mentioned: after a coagulant solution is attached to the substrate, it is immersed in a latex composition for forming another polymer layer at an arbitrary time, and then, after the other polymer layer is formed by appropriately drying and washing, a polymer layer formed from the latex composition of the present invention is formed thereon according to the above method.
[0134] The dip-molded article of the present invention has excellent oil grip and can be preferably used for gloves, particularly protective gloves. In the above, the dip-molded article of the present invention is described as an example of a laminate of a substrate and a polymer layer formed of a dip-molding latex composition. However, as described above, the present invention is not limited to such a form, and of course, a film-molded article formed of a dip-molding latex composition obtained by dipping a dip-molding mold in the dip-molding latex composition can also be prepared.
[0135] Example
[0136] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the following "parts" are weight references. In addition, various physical properties were measured as follows.
[0137] <Volume Average Particle Size>
[0138] The volume average particle size of the polymer particles constituting the latex of each polymer was measured using a light scattering diffraction particle measuring apparatus (manufactured by Beckman Coulter, trade name “LS-230”).
[0139] <Solid Content Concentration of Dip Molding Latex Composition>
[0140] 2 g of the sample (weight: X2) was accurately weighed in an aluminum pan (weight: X1) and dried in a hot air dryer at 105°C for 2 hours. After cooling in the dryer, the weight of the sample together with the aluminum pan was measured (weight: X3), and the solid content concentration was calculated according to the following calculation formula.
[0141] Solid content concentration (weight %) = (X3-X1) × 100 / X2
[0142] <Percentage of THF-insoluble components>
[0143] The latex of each polymer (polymer (A-1), (B-1) to (B-5)) was applied to a substrate by a casting method, and dried at 25°C for 120 hours to obtain a dry film, and the weight of the obtained dry film (W1 (kg)) was measured. Next, the obtained dry film was immersed in tetrahydrofuran at 25°C for 24 hours, and the immersed film was dried at 105°C for 3 hours to remove the tetrahydrofuran. Then, the weight of the film after the removal of tetrahydrofuran was measured (W2 (kg)), and the percentage of tetrahydrofuran insoluble components was calculated according to the following formula.
[0144] Percentage of tetrahydrofuran insoluble components (unit: weight %) = 100 × W2 (kg) / W1 (kg)
[0145] <Determination of Chemical Stability>
[0146] The latex of the conjugated diene polymer (A) and the latex of the polymer (B) were each diluted with distilled water so that the solid content concentration became 20% by weight.
[0147] In addition, a CaCl2 aqueous solution having the following concentrations was prepared using distilled water.
[0148] 0.01% by weight, 0.1% by weight, 0.2% by weight, 0.3% by weight, 0.5% by weight, 0.75% by weight, 1.0% by weight, 1.2% by weight
[0149] Weigh 6 to 7 g of the CaCl2 aqueous solution of the above concentration in a dish, and add 0.03 to 0.04 g of the latex diluted to 20% by weight. After the addition, let it stand for 1 minute and then shake it gently to mix. After mixing, visually judge the formation of coagulants. By taking the maximum concentration of the CaCl2 aqueous solution at which the formation of coagulants cannot be confirmed as the chemical stability of the polymer latex, the chemical stability of the latex of the conjugated diene polymer (A) (CS(A)) and the chemical stability of the latex of the polymer (B) (CS(B)) are calculated. Then, the difference in chemical stability (CS(B) - CS(A)) is calculated by subtracting the chemical stability of the latex of the conjugated diene polymer (A) (CS(A)) from the chemical stability of the latex of the polymer (B) (CS(B)).
[0150] <Oil grip>
[0151] Prepare metal models with different weights of 0.5kg to 15.0kg at intervals of 0.5kg. Then, ask three operators to wear protective gloves (impregnated molded bodies) and lift the metal models in a dry state one by one starting from the lighter side, and find out the maximum weight (W3 (kg)) that each of the three people can lift. Next, attach the test oil IRM903 to the metal model. Then, ask three operators to wear protective gloves (impregnated molded bodies) and lift the metal models with the test oil IRM903 attached to them one by one starting from the lighter side, and find out the maximum weight (W4 (kg)) that each of the three people can lift. Then, calculate the average score by taking the arithmetic average of the scores calculated by the following formula and evaluate. The higher the score, the greater the maximum weight that can be lifted, and it can be judged that the oil grip is better.
[0152] (fraction) = 100 × W3 (kg) / W4 (kg)
[0153] <Example 1>
[0154] (Preparation of Colloidal Sulfur Aqueous Dispersion)
[0155] 1.0 part of colloidal sulfur (manufactured by Hosoi Chemical Co., Ltd.), 0.5 part of a dispersant (manufactured by Kao Corporation, trade name "DEMOL N"), 0.0015 part of a 5 wt % aqueous potassium hydroxide solution (manufactured by Wako Pure Chemical Industries, Ltd.), and 1.0 part of water were pulverized and stirred in a ball mill for 48 hours to prepare an aqueous dispersion of colloidal sulfur having a solid content concentration of 50 wt %.
[0156] (Preparation of aqueous dispersion of zinc dibutyldithiocarbamate, aqueous dispersion of zinc oxide, and aqueous dispersion of titanium oxide)
[0157] An aqueous dispersion of zinc dibutyldithiocarbamate having a solid content of 50 wt %, an aqueous dispersion of zinc oxide having a solid content of 50 wt %, and an aqueous dispersion of titanium oxide having a solid content of 50 wt % were prepared in the same manner as above, except that zinc dibutyldithiocarbamate (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), zinc oxide (manufactured by Shodo Chemical Industry Co., Ltd.), and titanium oxide were used respectively in place of colloidal sulfur.
[0158] (Preparation of Latex of Nitrile Group-Containing Conjugated Diene Polymer (A-1))
[0159] In a polymerization reactor, 66 parts of 1,3-butadiene as a conjugated diene monomer, 30 parts of acrylonitrile as an α,β-ethylenically unsaturated nitrile monomer, 4 parts of methacrylic acid as an ethylenically unsaturated monocarboxylic acid monomer, 1 part of tert-dodecyl mercaptan, 200 parts of ion exchange water, 3 parts of sodium dodecylbenzenesulfonate, 1 part of β-naphthalenesulfonic acid formaldehyde condensate sodium salt, 0.1 part of potassium persulfate, and 0.1 part of ethylenediaminetetraacetic acid sodium salt are added, and the polymerization temperature is maintained at 30-40° C. to carry out polymerization, and the reaction is allowed to proceed until the polymerization conversion rate reaches 95%, thereby obtaining a latex of a copolymer.
[0160] Then, after removing the unreacted monomers from the obtained latex of the copolymer, the pH and solid content concentration of the latex of the copolymer were adjusted, thereby obtaining a latex of a nitrile group-containing conjugated diene polymer (A-1) having a solid content concentration of 45% by weight, pH=8.5, and CS(A)=0.1% by weight. The glass transition temperature (Tg) of the nitrile group-containing conjugated diene polymer (A-1) contained in the obtained latex of the nitrile group-containing conjugated diene polymer (A-1) was measured, and the result was -24°C. In addition, the volume average particle size of the particles of the nitrile group-containing conjugated diene polymer (A-1) constituting the latex of the nitrile group-containing conjugated diene polymer (A-1) was 126 nm, and the monomer composition of the nitrile group-containing conjugated diene polymer (A-1) was approximately the same as the charging ratio.
[0161] (Preparation of latex of polymethyl methacrylate resin (B-1))
[0162] In a polymerization reactor, 100 parts of methyl methacrylate, 6 parts of benzenesulfonate of 1,1'-oxybistetrapropylene derivative, 0.1 parts of tert-dodecyl mercaptan, 200 parts of ion exchange water, 1.5 parts of potassium persulfate, and 0.1 parts of ethylenediaminetetraacetic acid sodium salt are added, and the polymerization temperature is maintained at 30-70°C for polymerization, and the reaction is carried out until the polymerization conversion rate reaches 95%, thereby obtaining a polymer latex.
[0163] Then, by adjusting the pH and solid content concentration of the latex of the polymer, a latex of polymethyl methacrylate resin (B-1) having a solid content concentration of 30% by weight, pH = 8.5, and CS (B) = 1.0% by weight was obtained. The glass transition temperature (Tg) of polymethyl methacrylate resin (B-1) contained in the obtained latex of polymethyl methacrylate resin (B-1) was measured and found to be 123° C. The volume average particle size of the particles of polymethyl methacrylate resin (B-1) constituting the latex of polymethyl methacrylate resin (B-1) was 77 nm.
[0164] (Preparation of latex composition for dip molding)
[0165] The latex of the nitrile-containing conjugated diene polymer (A-1) obtained above and the latex of the polymethyl methacrylate resin (B-1) were mixed in a weight ratio of "nitrile-containing conjugated diene polymer (A-1): polymethyl methacrylate resin (B-1)" of 7:3, and 5 weight % of potassium hydroxide was added to prepare a latex composition having a solid content concentration of 46 weight % and a pH of 8.9.
[0166] Then, 1.0 part of colloidal sulfur, 1.0 part of zinc dibutyl dithiocarbamate, 1.5 parts of zinc oxide, and 3.0 parts of titanium oxide were added to the aqueous dispersion of each compounding agent prepared above in terms of solid content, respectively, with respect to 100 parts of the polymer component of the latex composition obtained above. When the aqueous dispersion of each compounding agent was added, a predetermined amount was slowly added while stirring the latex composition. Then, after each compounding agent was uniformly mixed, 1.2 parts of carboxymethyl cellulose (manufactured by Daicel Corporation, trade name "Daicel 2200", weight average molecular weight: 550000, acid content: 3.7 mmol / g) as a water-soluble polymer was added to adjust the solid content concentration, thereby obtaining a latex composition (I) for dip molding having a solid content concentration of 44% by weight, a viscosity of 3000 mPa·s at 25°C, and (CS(B)-CS(A))=0.9.
[0167] (Preparation of latex composition for dip molding (II))
[0168] The aqueous dispersion of each compounding agent prepared above was added in the form of 1.0 part of colloidal sulfur, 1.0 part of zinc dibutyl dithiocarbamate, 1.5 parts of zinc oxide, and 3.0 parts of titanium oxide, respectively, in terms of solid content, to 100 parts of the polymer component of the latex of the nitrile group-containing conjugated diene polymer (A-1). When adding the aqueous dispersion of each compounding agent, a predetermined amount was slowly added while stirring the latex composition. After each compounding agent was uniformly mixed, 0.3 parts of carboxymethyl cellulose (manufactured by Daicel Corporation, trade name "Daicel 2200", weight average molecular weight: 550000, acid content: 3.7 mmol / g) as a water-soluble polymer was added to adjust the solid content concentration, thereby obtaining a latex composition for dip molding (II) having a solid content concentration of 43% by weight and a viscosity of 3000 mPa·s at 25°C.
[0169] (Preparation of coagulant solution)
[0170] A coagulant solution was prepared by dissolving calcium nitrate as a coagulant in methanol at a ratio of 3.0 wt%.
[0171] (Manufacture of protective gloves (dip molded articles) having a single polymer layer)
[0172] First, the latex composition (I) for dip molding obtained above was aged (also called pre-vulcanization) at a temperature of 30°C for 48 hours. Next, a ceramic glove mold covered with a fiber substrate in the shape of a glove (material: nylon, linear density: 300 denier, number of needles: 13 needles, thickness: 0.8 mm) was immersed in the coagulant solution prepared above for 5 seconds, pulled out of the coagulant solution, and dried at a temperature of 30°C for 1 minute. Thereafter, the ceramic glove mold was immersed in the latex composition (I) for dip molding above for 5 seconds, pulled out of the latex composition (I) for dip molding, and dried at a temperature of 30°C for 30 minutes, and then heated at a temperature of 70°C for 10 minutes to perform crosslinking, thereby forming a polymer layer with a film thickness of 0.6 mm on the fiber substrate. After that, the ceramic glove mold on which the polymer layer was formed was dried at a temperature of 30°C for 10 minutes, and then heat-treated at a temperature of 125°C for 30 minutes, thereby subjecting the polymer in the polymer layer to a cross-linking treatment. Next, the fiber substrate on which the polymer layer was formed was peeled off from the ceramic glove mold to obtain a protective glove (impregnated molded body) having a single polymer layer. Then, the obtained protective glove (impregnated molded body) was used to measure the oil grip according to the above method. The results are shown in Table 1.
[0173] (Manufacture of protective gloves (dip molded article) having two polymer layers)
[0174] First, the latex composition (II) for dip molding obtained above was aged (also called pre-vulcanization) at a temperature of 30°C for 48 hours. Next, a ceramic glove mold covered with a glove-shaped fiber substrate (material: nylon, linear density: 300 denier, number of needles: 13 needles, thickness: 0.8 mm) was immersed in the coagulant solution prepared above for 5 seconds, pulled out of the coagulant solution, and dried at a temperature of 30°C for 1 minute. Thereafter, the ceramic glove mold was immersed in the latex composition (II) for dip molding for 5 seconds, pulled out of the latex composition (II) for dip molding, and dried at a temperature of 30°C for 30 minutes, thereby forming an impregnation layer (first impregnation layer) containing a nitrile group-containing conjugated diene polymer on the fiber substrate. Then, the ceramic glove mold formed with the first impregnation layer was dried at a temperature of 70°C for 20 minutes.
[0175] The obtained latex composition for dip molding (I) was aged (also referred to as pre-vulcanization) at a temperature of 30 degrees for 48 hours. Next, the ceramic glove mold having the first impregnation layer formed thereon was dipped in the above-mentioned latex composition for dip molding (I) for 5 seconds, pulled out of the latex composition for dip molding (I), and then dried at a temperature of 30 degrees for 30 minutes, thereby forming an impregnation layer (second impregnation layer) containing the nitrile group-containing conjugated diene polymer (A-1) and the polymethyl methacrylate resin (B-1) on the first impregnation layer.
[0176] After that, the ceramic glove mold on which the first impregnation layer and the second impregnation layer were formed was dried at a temperature of 30° C. for 10 minutes, and then heat-treated at a temperature of 125° C. for 30 minutes, thereby subjecting the polymers in the first impregnation layer and the second impregnation layer to a cross-linking treatment, thereby forming the first polymer layer and the second polymer layer, respectively. Next, by peeling the fiber substrate on which the first polymer layer and the second polymer layer were formed from the ceramic glove mold, a protective glove (impregnation molded body) having two polymer layers with a thickness of 0.13 mm for the first polymer layer, a thickness of 0.03 mm for the second polymer layer, and a total thickness of 0.16 mm for the first polymer layer and the second polymer layer was obtained.
[0177] Then, the protective gloves (dipping molded body) having the obtained two polymer layers were used to evaluate the oil grip property.
[0178] <Example 2>
[0179] A latex composition for dip molding (III) was obtained in the same manner as in Example 1 except that the solid content concentration of the latex composition for dip molding was changed to 38% by weight. A protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having two polymer layers were obtained in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0180] <Example 3>
[0181] A latex composition for dip molding (IV) was obtained in the same manner as in Example 1, except that the mixing ratio of the latex of the nitrile group-containing conjugated diene polymer (A-1) and the latex of the polymethyl methacrylate resin (B-1) was 5:5 in terms of the weight ratio of "nitrile group-containing conjugated diene polymer (A-1): polymethyl methacrylate resin (B-1)" and the solid content concentration was 35% by weight. A protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having two polymer layers were obtained in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0182] <Example 4>
[0183] (Preparation of latex of polymethyl methacrylate resin (B-2))
[0184] In a polymerization reactor, 100 parts of methyl methacrylate, 6 parts of benzenesulfonate of a 1,1'-oxybistetrapropylene derivative, 0.1 parts of tert-dodecyl mercaptan, 200 parts of ion exchange water, 0.3 parts of potassium persulfate, and 0.1 parts of sodium salt of ethylenediaminetetraacetic acid are added, and the polymerization temperature is maintained at 30 to 70° C. for polymerization to react until the polymerization conversion rate reaches 95%, thereby obtaining a polymer latex.
[0185] Then, by adjusting the pH and solid content concentration of the latex of the polymer, a latex of polymethyl methacrylate resin (B-2) having a solid content concentration of 30% by weight, pH = 8.5, and CS (B) = 0.5 was obtained. The glass transition temperature (Tg) of polymethyl methacrylate resin (B-2) contained in the obtained latex of polymethyl methacrylate resin (B-2) was measured and found to be 123° C. The volume average particle size of the particles of polymethyl methacrylate resin (B-2) constituting the latex of polymethyl methacrylate resin (B-2) was 106 nm.
[0186] Then, a latex composition (V) for dip molding having (CS(B)-CS(A))=0.4 was prepared in the same manner as in Example 1 except that a latex of a polymethyl methacrylate resin (B-2) was used instead of a latex of a polymethyl methacrylate resin (B-1) and that the solid content concentration of the latex composition for dip molding was changed to 38% by weight, and a protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having a double polymer layer were obtained and evaluated in the same manner. The results are shown in Table 1.
[0187] <Example 5>
[0188] (Preparation of Latex of Methyl Methacrylate-Styrene Copolymer Resin (B-3))
[0189] In a polymerization reactor, 40 parts of methyl methacrylate, 60 parts of styrene, 6 parts of benzenesulfonate of 1,1'-oxybistetrapropylene derivative, 0.1 parts of tert-dodecyl mercaptan, 200 parts of ion exchange water, 1.5 parts of potassium persulfate, and 0.1 parts of ethylenediaminetetraacetic acid sodium salt are added, and the polymerization temperature is maintained at 30-70°C for polymerization, and the reaction is allowed to proceed until the polymerization conversion rate reaches 90%, thereby obtaining a polymer latex.
[0190] Then, after removing the unreacted monomers from the obtained polymer latex, the pH and solid content concentration of the polymer latex were adjusted to obtain a latex of methyl methacrylate-styrene copolymer resin (B-3) having a solid content concentration of 30% by weight and a pH of 8.5. The glass transition temperature (Tg) of the methyl methacrylate-styrene copolymer resin (B-3) contained in the obtained latex of the methyl methacrylate-styrene copolymer resin (B-3) was measured and found to be 104°C. In addition, the volume average particle size of the particles of the methyl methacrylate-styrene copolymer resin (B-3) constituting the latex of the methyl methacrylate-styrene copolymer resin (B-3) was 75 nm.
[0191] Then, a latex composition (VI) for dip molding having (CS(B)-CS(A))=0.1 was prepared in the same manner as in Example 1 except that a latex of a methyl methacrylate-styrene copolymer resin (B-3) was used instead of the latex of the polymethyl methacrylate resin (B-1) and that the solid content concentration of the latex composition for dip molding was 39% by weight. A protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having a double polymer layer were obtained in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0192] <Comparative Example 1>
[0193] A latex composition (VII) for dip molding in which (CS(B)-CS(A))=0 was prepared in the same manner as in Example 1 except that a latex of polyvinyl chloride (B-4) (trade name "VINYBLAN985", manufactured by Nissin Chemical Industry Co., Ltd., glass transition temperature (Tg) of polyvinyl chloride (B-4) is 80°C, volume average particle size of particles of polyvinyl chloride (B-4) is 84 nm, CS(B)=0.1, and polyvinyl chloride (B-4) contains substantially no plasticizer) was used instead of the latex of polymethyl methacrylate resin (B-1), and the solid content concentration of the latex composition for dip molding was 42% by weight. A protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having a double polymer layer were obtained in the same manner as in Example 1, and were evaluated in the same manner. The results are shown in Table 1.
[0194] <Comparative Example 2>
[0195] (Preparation of latex of polystyrene resin (B-5))
[0196] In a polymerization reactor, 100 parts of styrene, 6 parts of benzenesulfonate of a 1,1'-oxybistetrapropylene derivative, 0.1 parts of tert-dodecyl mercaptan, 200 parts of ion exchange water, 1.5 parts of potassium persulfate, and 0.1 parts of sodium salt of ethylenediaminetetraacetic acid are added, and the polymerization temperature is maintained at 30 to 70° C. for polymerization, and the reaction is allowed to proceed until the polymerization conversion rate reaches 90%, thereby obtaining a polymer latex.
[0197] Then, by adjusting the pH and solid content concentration of the latex of the polymer, a latex of a polystyrene resin (B-5) having a solid content concentration of 30% by weight, pH = 8.5, and CS (B) = 0.01% by weight was obtained. The glass transition temperature (Tg) of the polystyrene resin (B-5) contained in the obtained latex of the polystyrene resin (B-5) was measured and found to be 92° C. In addition, the volume average particle size of the particles of the polystyrene resin (B-5) constituting the latex of the polystyrene resin (B-5) was 74 nm.
[0198] Then, a latex composition (VIII) for dip molding having (CS(B)-CS(A))=-0.09 was prepared in the same manner as in Example 1 except that a latex of a polystyrene resin (B-5) was used instead of a latex of a polymethyl methacrylate resin (B-1) and that the solid content concentration of the latex composition for dip molding was 39% by weight. A protective glove (dip molded article) having a single polymer layer and a protective glove (dip molded article) having a double polymer layer were obtained in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0199] [Table 1]
[0200]
[0201] As shown in Table 1, if the latex composition contains a latex of a conjugated diene polymer (A) having a glass transition temperature of less than 10°C and a latex of a polymer (B) having a glass transition temperature greater than 10°C, and the difference between the chemical stability of the latex of the conjugated diene polymer (A) relative to CaCl2 (CS(A)) and the chemical stability of the latex of the polymer (B) relative to CaCl2 (CS(B)) ((CS(B)-CS(A))) is greater than 0 weight %, the obtained impregnated molded body has excellent oil grip regardless of whether it has only a single layer or two layers (Examples 1 to 5).
[0202] On the other hand, when the difference in chemical stability (CS(B)-CS(A)) was 0 or less, the obtained dip-molded body had poor oil grip (Comparative Examples 1 and 2).
Claims
1. A latex composition comprising a latex of a conjugated diene polymer (A) having a glass transition temperature of 10°C or less and a latex of a polymer (B) having a glass transition temperature of more than 10°C, The polymer (B) is a homopolymer of acrylate, a homopolymer of methacrylate, a homopolymer of acrylic acid or a homopolymer of methacrylic acid, The volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is smaller than the volume average particle size of the particles of the conjugated diene polymer (A) contained in the latex of the conjugated diene polymer (A), The solid content concentration of the latex composition is 30% by weight or more, The content ratio of the conjugated diene polymer (A) to the polymer (B) is 1:9 to 9:1, based on the weight ratio of "conjugated diene polymer (A): polymer (B)". The chemical stability to CaCl2 when the solid content concentration of the latex of the conjugated diene polymer (A) is 20 wt% is denoted as CS(A) (wt%), When the chemical stability of the latex of the polymer (B) with respect to CaCl2 when the solid content concentration is 20 wt % is defined as CS (B) (wt %), The value of (CS(B)-CS(A)) is greater than 0 wt%.
2. The latex composition according to claim 1, wherein The volume average particle diameter of the polymer particles contained in the latex composition is 250 nm or less.
3. The latex composition according to claim 2, wherein The volume average particle size of the polymer particles is 200 nm or less.
4. The latex composition according to any one of claims 1 to 3, wherein The volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is 200 nm or less.
5. The latex composition according to claim 4, wherein The volume average particle size of the particles of the polymer (B) contained in the latex of the polymer (B) is 100 nm or less.
6. The latex composition according to any one of claims 1 to 3, wherein The polymer (B) has a sulfate group as a residue of a polymerization initiator at the polymer chain terminal.
7. The latex composition according to any one of claims 1 to 3, wherein The conjugated diene polymer (A) includes at least one selected from styrene-butadiene rubber, nitrile rubber, and polyisoprene rubber.
8. The latex composition according to any one of claims 1 to 3, wherein The conjugated diene polymer (A) is a carboxyl group-containing conjugated diene polymer. 9 . A dip-molded article obtained by dip-molding the latex composition according to claim 1 .
10. The impregnated molded body according to claim 9, wherein The dip-molded body is a glove.
Citation Information
Patent Citations
Method for producing laminate
WO2018061868A1
Carbonic acid modified nitrile copolymer latex for dip molding, latex composition for dip molding including same, and molded part manufactured from the composition
CN103930479A
Carboxylic acid modified-nitrile based copolymer composition and dip-form article thereof
KR1020130055334A